Economic burden of multiple sclerosis: A cross-sectional study in Iran - Mehdi Rezaee; Khosro Keshavarz; Sadegh Izadi; Abdosaleh Jafari; Ramin Ravangard (Health Economics Review, 2022)
Background: Multiple Sclerosis (MS) is a chronic debilitating disease that imposes a heavy socioeconomic burden on societies. This study aimed to determine the economic burden of MS on patients using the first (CinnoVex and ReciGen) and second (Fingolimod and Natalizumab) drug therapy lines. Methods: This cost of illness study was an economic evaluation carried out as cross-sectional research in 2019 in southern Iran. A total of 259 patients were enrolled in two lines of drug therapy (178 patients in the first line and 81 ones in the second). The prevalence-based approach and the bottom-up approach were used to collect cost information and to calculate the costs from the societal perspective, respectively. The human capital approach was applied to calculate indirect costs. To collect the required data a researcher-made data collection form was utilized. The data were obtained using the information available in the patients' medical records and insurance invoices as well as their self-reports or that of their companions. Results: The results showed that the annual costs of MS in the first and second lines of drug therapy per patient were 1919 and 4082 purchasing power parity (PPP), respectively, and in total, 2721 PPP in 2019. The highest mean costs in both lines were those of direct medical costs, of which purchasing the main medicines in both lines accounted for the highest. Conclusion: Considering the findings of this study and in order to reduce the burden of the disease, the following suggestions are presented: providing necessary facilities for the production of MS drugs in the country; proper and equitable distribution of neurologists; expanding the provision of home care services; and using the technologies related to the Internet, including WhatsApp, to follow up the MS patients' treatment.
Keywords: 330; Economic burden; Multiple sclerosis (MS); Direct medical costs; Direct non-medical costs; Indirect costs